Introduction to public history interpreting the past, engaging audiences - Lyon, Cherstin M.; Nix, Elizabeth M.; Shrum, Rebecca K. (Rebecca Kathleen) (Rowman & Littlefield, 2017)
Introduction to Public History: Interpreting the Past, Engaging Audiences is a brief foundational textbook for public history. It is organized around the questions and ethical dilemmas that drive public history in a variety of settings, from local community-based projects to international case studies. This book is designed for use in undergraduate and graduate classrooms with future public historians, teachers, and consumers of history in mind.